CEPHALOMETRIC STUDIES OF UKRAINIAN BOYS AND GIRLS WITH ORTHOGNATHIC BITE BY THE METHOD OF R. M. RICKETTS - Chernysh, A.V.; Gunas, І.V.; Gavryluk, A.O.; Dmytrenko, S.V.; Serebrennikova, O.A.; Kyrychenko, Yu.V.; Balynska, M.V. (World of Medicine and Biology, 2018)
According to literary sources, most of the cephalometric parameters obtained by the Ricketts method have age and gender differences, as well as significantly depend on the ethnicity and climatogeographical features of the region. That is why, before planning any orthodontic procedures, one cannot underestimate the cephalometric norms developed for different ethnic and age groups of the population. The purpose of the study is to establish and analyze the cephalometric parameters by the method of R.M. Ricketts in boys and girls of the Podillia region of Ukraine with orthognathic bite. Primary lateral teleroentgenograms of 38 young men and 55 girls with normal occlusion close to orthognathic bite, obtained using the Veraviewepocs 3D device, Morita (Japan), were taken from the data bank of the research center of the National Pirogov Memorial Medical University, Vinnytsya. Cephalometric measurements were performed according to the recommendations of R.M. Ricketts. Statistical processing of the obtained results was carried out in the licensed package "Statistica 6.0" using nonparametric methods for evaluating the obtained results. In analyzing the gender differences in cephalometric parameters obtained by the Ricketts method “Ricketts comprehensive computer description analysis” in boys with normal occlusion close to orthognathic bite, only for Canine Relation, Upper Molar Position, Upper Lip Length, Cranial Length - Anterior, Posterior Facial Height, Porion Location and Corpus Length. When comparing cephalometric parameters in boys and girls of Podillia with orthognathic bite with the magnitude of these parameters obtained by R. M. Ricketts, most indicators in both boys and girls have pronounced differences. Thus, the results obtained by us allow the orthodontist to predict both the growth and the changes obtained in the course of treatment of the parameters of the facial part of the head.
Keywords: lateral teleroentgenograms of head; cephalometry; boys and girls Podillia with orthognathic bite; R. M. Ricketts analysis